(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aims to assess the knowledge, attitudes, and practices regarding school myopia prevention among preventive medicine students at Thai Nguyen University of Medicine and Pharmacy in the 2024-2025 academic year. Materials and methods: A cross-sectional study was conducted on 266 students using a survey questionnaire, with data analyzed using SPSS 26.0 software. Results: 57.1% of students had correct knowledge about myopia prevention. Common risk factors included reading while lying down (100%), reading at a very close distance (94.4%), and prolonged use of electronic devices (86.1%). However, understanding of the role of vitamin D (29.3%) and genetic factors (48.1%) remained limited. Regarding attitudes, 97,3% of students showed concern for myopia prevention, demonstrating awareness of eye protection. In terms of practice, 89.1% followed proper measures, particularly maintaining correct sitting posture (92.5%), studying in well-lit environments (91.7%), and avoiding reading while lying down (98.1%). However, habits such as practicing distance vision (71.4%) and limiting screen time (77.1%) still need improvement. Conclusions: Although most students have good practice, knowledge still needs to be improved. Additional educational programs on nutrition and genetic factors in myopia are needed.